Utilização do efeito Peltier para resfriamento de ambientes - Silva, Thaynara Pedrosa (2021)
In a world where the global warming exists, the global population is increasingly seeking a thermal comfort through the air cooling systems. The most usual system found in houses and buildings is the air conditioners, which release HFCs and CO2, gases harmful to the environment. To avoid these problems, this work uses the Peltier effect, which consists of generating a temperature gradient when an electrical current passes through two semiconductor elements, to cool environments without emitting toxic gases into the atmosphere. Environment prototypes were produced by sheets of Styrofoam with thickness equal to 25 mm, with base areas ranging from 0.20 m2 to 1.70 m2 and a constant ceiling height of 0.25 m. The cooling system had four Peltier cells connected to an electrical source of 50 A and 12 V and their powers ranged from 285.8 W to 334.2 W. The heat dissipation on the hot side of the system was done by an aluminum heat sink with a stream of water at its base and a fan blowing on its fins. On the cold side, the dissipation was exclusively made by a second aluminum heat sink and a fan circulating the air in the environment. Five thermometers were placed in different locations to analyze the behavior of indoor air. The tests happened for 120 minutes, but the greatest drops in temperature were in the first 20 minutes. The best result was in the environment with the smallest base area and the greater power, where a drop of 9.4 ºC was recorded. It also was noticed that the fan inside the environments influenced the cooling, as it produced heat. Testing in three different areas showed that the smaller the environment, the higher was the effect of the fan’s heat.